High sodium diet intake and cardiovascular diseases: An attributable death study in Tianjin, China. Issue 1 (29th November 2022) - Xue, Xiao‐Dan; Li, Wei; Xie, Mei‐Qiu; Wang, De‐Zheng; Li, Dan‐Dan; Xin, Peng; Zheng, Wen‐Long; Jiang, Guo‐Hong
Abstract: There is clear evidence that high sodium intake is associated with many health issues including hypertension and cardiovascular diseases (CVDs). Several national and worldwide studies have estimated deaths from CVDs attributable to high sodium. But how to evaluate the impact of high sodium intake on diseases using regional routine monitoring and investigation data is necessary and important. Our study aimed to quantitatively evaluate the high sodium intake attributed to CVDs deaths based on the routine monitoring data from China National Nutrition and Health Survey (CNNHS) in Tianjin, China. The population attributable fractions (PAF) were calculated by comparing the observed systolic blood pressure (SBP) distribution with the theoretical minimum or counterfactual distribution by sex and age groups. The results showed that CVDs deaths due to elevated SBP were 22728 (95% uncertainty intervals: 22679‐23050), accounting for 62.8% of total CVDs deaths. According to sodium intake recommended by World Health Organization (WHO), PAF of CVDs deaths attributable to high sodium diet in our study was 14.6% of total CVDs deaths, accounting for 5228 (95% UI: 5005–5998) cases. The dietary sodium intake of residents is nearly three times than sodium intake recommended by WHO. If sodium intake was reduced to reference level, the potential avoidable CVD deaths attributable to the SBP‐raising effect were more than 5200 among adults 25 aged and over in Tianjin. This evaluation method can be extended to other cities.